2013
DOI: 10.1002/art.37795
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and sociodemographics of systemic lupus erythematosus and lupus nephritis among US adults with Medicaid coverage, 2000–2004

Abstract: Objective Systemic lupus erythematosus (SLE) and lupus nephritis (LN) disproportionately affect racial/ethnic minorities and lower socioeconomic status (SES) individuals. We investigated the epidemiology and sociodemographics of SLE and LN in the low-income U.S. Medicaid population. Methods We utilized Medicaid Analytic eXtract data, with billing claims from 47 states and Washington, D.C. for 23.9 million individuals, aged 18–65 years, enrolled in Medicaid for >3 months, 2000–2004. Individuals with SLE (> 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
336
5
12

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 416 publications
(375 citation statements)
references
References 49 publications
(58 reference statements)
22
336
5
12
Order By: Relevance
“…This study found an unusually high prevalence and incidence that is likely to reflect the nature of the inclusion criteria (i.e. limited to Medicaid users) and is discussed later in this review in the context of the influence of social deprivation 28 .In contrast two state-based studies, the Georgia Lupus Registry 72 and the Michigan Lupus Epidemiology and Surveillance Program 127 , identified potential cases from a wider range of sources, albeit over narrower geographical areas. The overall age-adjusted incidence rate was 5.6 per 100,000 per year for the Georgia Lupus Registry and 5.5 per 100,000 per year for the Michigan study, with an ageadjusted prevalence rate of 73 per 10, 000 reported for both studies.…”
mentioning
confidence: 78%
“…This study found an unusually high prevalence and incidence that is likely to reflect the nature of the inclusion criteria (i.e. limited to Medicaid users) and is discussed later in this review in the context of the influence of social deprivation 28 .In contrast two state-based studies, the Georgia Lupus Registry 72 and the Michigan Lupus Epidemiology and Surveillance Program 127 , identified potential cases from a wider range of sources, albeit over narrower geographical areas. The overall age-adjusted incidence rate was 5.6 per 100,000 per year for the Georgia Lupus Registry and 5.5 per 100,000 per year for the Michigan study, with an ageadjusted prevalence rate of 73 per 10, 000 reported for both studies.…”
mentioning
confidence: 78%
“…The prevalence of SLE and the chances of developing lupus nephritis (LN) vary considerably between different regions of the world and different races and ethnicities (Table 1) (2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In the United States, the higher frequency of LN in black populations persists after adjustment for socioeconomic factors (15). Additionally, black and Hispanic SLE patients develop LN earlier (16), and have worse outcomes than white patients with SLE, including death and ESRD (10).…”
Section: Epidemiologymentioning
confidence: 99%
“…Age of presentation is typically around the third decade, more likely in females of African, Hispanic, and Asian origin [1]. The most common initial symptoms include fever, arthralgia, and malar rash.…”
Section: Introductionmentioning
confidence: 99%